PENGARUH DAILY BEHAVIOUR REPORT CARD TERHADAP PENURUNAN PERILAKU MALADAPTIF PESERTA DIDIK MULTIPLE DISABILITIES WITH VISUAL IMPAIRMENT - Rizqi Wahyuni SW, - (2018)
Pesertadidikmultiple disabilities with visual impairmentpadaanakdenganhambatanlow visiondisertaiattention deficit hiperaktivedisorder padaumumnyamemilikiperilakumaladaptifsalahsatunyayaituperilakuhiperaktivitas. Hal tersebutdapatmenjadimasalahbagipesertadidikdalammemusatkanperhatianterhadappelajaransehinggaakanmenimbulkankesukaranpembelajaran di dalamkelas. Penelitianinibertujuanuntukmengetahuipengaruhmetodedaily behavior report cardterhadappenurunanperilakumaladaptifpesertadidikMultiple Disabilities with Visual Impairment. Metodepenelitian yang digunakanadalaheksperimenSingle Subject Reseach(SSR), dengandesainpenelitian A-B-A. Penelitianinidilakukanterhadapsatupesertadidikberinisial TSD kelasIII SDLB di SLB NegeriA Kota Bandung. Teknikpengumpulan datayang digunakandalampenelitianiniadalahobservasi. Terdapattigafasedalampengumpulan data, pertamabaseline 1, keduaintervensidanketigabaseline 2. Hasilpenelitianmenunjukanbahwa mean level padafasebaseline-1 (27,67),intervensi (23,14)danbaseline 2 (21,33) mengalamipenurunanpadaperilakuberbicarakasarpada guru, perilakuberbicarakasarpadatemansebaya, perilakumemotongpembicaraan guru, perilakumengalihkanpembicaraanmengenaimateripembelajaran yang sedangberlangsung, perilakuberbicaradengandirinyasendiridanperilakumengajakberbicara orang lain ketika proses pembelajaranberlangsung. Dengandemikianbahwametodedaily behavior report card berpengaruhterhadappenurunanperilakumaladaptifpesertadidikMultiple Disabilities with Visual Impairment.;--- Student with multiple disabilities visual impairment on children with low vision dissabilities accompanied by attention deficit hiperaktive disorder generally have one of maladaptif behavior for example hyperactivity behavior. It can be a problem for student in focussing of attention to the lesson and it will cause difficulty learning in the classroom. This research aims to know the influence of daily behavior report cards method against decrease in behavior of student with maladaptif Multiple Disabilities Visual Impairment. The research method used is experimentation Single Subject Reseach (SSR), using research A-B-A. This research was conducted for each learner the initials TSD class III SDLB at SLB NegeriA Bandung. Data collection techniques used in this research is the observation. There are three phases in data collection, baseline 1 first, second and third intervention baseline 2. The research results showed that the mean level in the baseline phase-1 (27,67) intervention (23,14) and baseline 2 (21,33) has decreased on the behavior of a rough talk on teacher behavior, behavior speak harshly on peers, teacher talk, cutting behavior behavior turned his conversation about ongoing learning materials, conduct talks with himself and the behavior of the invited talk others when the learning process takes place. Thus that the method of daily behavior report cards to decrease behavior maladaptif Multiple Disabilities learners with Visual Impairment.